Ukrepi za preprečevanje padcev pri starejših odraslih v domačem okolju - Juder, Gregor (Obzornik zdravstvene nege, 2024)
Introduction: Community nurses perform risk assessments of falls in older adults and advise them on appropriate measures to prevent falls in the home environment. The aim of this study was to explore the most effective measures to prevent falls and the most common risk factors for falls in the home environment.Methods: A review of the scientific literature was conducted in the PubMed, Science Direct and SAGE databases along with a qualitative content analysis and synthesis. The literature search took place from 10 April to 11 October 2019. The literature review was conducted following the PRISMA guidelines.Results: Of the 347 search hits, 11 original scientific articles and literature reviews were selected for the final analysis. One article was classified at level 1 and ten at level 4. We identified one main category, namely Falls in Older Adults, and three subcategories: (1) Frequency of Falls, (2) Risk Factors, and (3) Measures to Prevent Falls. We identified several factors that contribute to an increased risk of falls among healthy individuals aged 65 and above, as well as effective measures to prevent falls in the home environment.Discussion and conclusion: As falls cause health-related, social and economic consequences, there are still numerous unexplored opportunities in this field. A comprehensive understanding of the risk factors and measures to prevent falls is extremely important for community nurses as it improves the quality of care for older adults in community nursing and promotes its integration and safety. This study contributes to improving clinical practice when working with older adults in the home environment.
Keywords: community nursing; nevarnost padcev; older adults; patronažno varstvo; preventiva; preventive measures; risk of falls; starejši